Investigating Reliability of Duimenshan High Rock Slope in Gejiu, Yunnan Province Based on the Monte Carlo Method - A. Fa-You; Wan-cheng Pan; Wen-ping Wu; Shi-qun Yan (Geofluids)
A slope is a complex engineering geological body that contains many uncertainties. In the present study, the high rock slope of Duimenshan in Gejiu, China is taken as the research object, and the Monte Carlo method is used to perform the analyses. Firstly, based on a large number of rock mass discontinuities, the Fuzzy C-Means (FCM) clustering algorithm is used to determine the dominant discontinuities. Secondly, the affecting parameters of the rock mass such as cohesion, internal friction angle, horizontal seismic acceleration coefficient, and water-filled depth coefficient are taken as random variables, and the failure probability of the slope and the failure index corresponding to different slope heights and slopes are obtained as the output parameter. The obtained results show that the target reliability index of the slope in a certain range of the slope height is far from the safety value, indicating that the slope is unstable, and the combination of slope height and slope angle affects the reliability of the slope. More specifically, as the slope height and angle increase, the number of samples with a stability coefficient of less than 1 increases, thereby increasing the failure probability of the slope indicating that the slope is stable. It is found that unless the slope height is small, it is the main factor of stability. However, when the slope height exceeds 33 m, the effect of the slope inclination on the stability increases gradually.